Hadist Tematik Komunikasi Pembangunan: Konsep “Masjid” dan “Kerja” - Andi Kardian Riva'i (LPPM STISIP Persada Bunda, 2022)
This study focuses on the purpose of describing the meaning of religious symbols in the concept of development communication, especially with an Islamic perspective approach which is interpreted as a symbol that is cult and sacred by society, especially Islam. The compilation method is based on library research and the software program Encyclopedia Hadith 9 Imam accesses nine books of primary sources of hadith to facilitate the completion of the critical method of sanad and subject of this study. There are two substances in the discussion that was built, namely: first,